"A Necessary Investment in Future Health": Perceptions of Physical Activity Maintenance Among People With Rheumatoid Arthritis. Issue 12 (24th September 2020) - Swärdh, Emma; Nordgren, Birgitta; Opava, Christina H; Demmelmaier, Ingrid
Abstract: Objective: A few studies with a qualitative design have addressed physical activity (PA) maintenance in people with rheumatoid arthritis (RA), but none of them focused specifically on maintenance of PA according to public health recommendations. The purpose of this study was to describe perceptions of PA maintenance during the second year of an outsourced 2-year support program among people with RA. Methods: For this descriptive design with a qualitative inductive approach, semi-structured interviews were conducted with 18 participants with RA (3 men and 15 women). Variation in age, disease duration, activity limitation, pain, levels of PA, and PA maintenance was targeted through strategic sampling. Qualitative content analysis was used, and a pattern of theme, subthemes, and categories was constructed based on the participants' perceptions of PA maintenance. Results: A main overarching theme, "A necessary investment in future health"—with 3 subthemes of dedication, awareness, and affinity —was identified as participants' perceptions of PA maintenance. Eight categories further described are a changed mindset, habits, commitments, monitoring, insights in PA, health gains, social support, and PA context. Conclusions: PA according to public health recommendations was perceived as a true investment in future health and wellness requiring dedication, awareness, and affinity. To promote PA maintenance, physical therapists working with people with chronic conditions should consider strengthening these prerequisites by targeting patients' negative attitudes to PA, supporting their creation of PA habits to incorporate in daily routines, introducing monitoring of PA intensity, supporting development of PA self-regulation skills, and providing suitable gym facilities with the possibility of peer support.